Parliaments, Estates and Representation — Parlements, Etats et Représentation, ed. by J. Rogister, vol. I (1981), vol. II (1982) - Russocki, Stanisław (Czasopismo Prawno-Historyczne, 1983)
Recenzja: Parliaments, Estates and Representation — Parlaments, Etats et Representation, ed. by J. Rogister, published for the International Commission for the History of Representative and Parliamentary Institutions by Pageant Publishing, London, vol. I (1981), ss. 190, vol. II (1982), ss. 192.